INTERPRETASI KONTEKS PRAGMATIK DALAM PEMELAJARAN BAHASA - Kunjana Rahardi (LITERASI: Indonesian Journal of Humanities, 2011)
Pragmatics as the waste basket of linguistics –because this field of language study becomes the receiver of any unsolved linguistics problems– needs to accommodate the broadest understanding of the contexts themselves. Not only that it must include the so-called textual context and any extralinguistics ones such as the spatio-temporal settings, but it also includes ones that relate to social and cultural aspects. Comprehensive, wise, and through considerations on any situational aspects of the utterances, in addition to social and cultural aspects, might also determine the right interpretation of meanings of the language. All aspects of contexts that might be utilized and implemented comprehensively to interprete meanings of any unsolved linguistics items might be called in this way, the pragmatics context. The last mentioned is the main concern of the discussion of this article and definitely such context needs to be reinterpreted. Keywords: pragmatics, waste basket, pragmatic contexts, reinterpretation